2014
DOI: 10.1186/1471-2458-14-769
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression in adults with type 2 diabetes in the Basque Country: relationship with glycaemic control and health care costs

Abstract: BackgroundThe aim of the study was to estimate the prevalence of depression in the population diagnosed with diabetes type 2 and to test the hypothesis that the presence of depression in such cases was associated with a) worse glycaemic control, and b) higher healthcare costs.MethodsWe conducted a cross-sectional analysis, from 1st September 2010 to 31st August 2011, among patients with type 2 diabetes aged 35 years and over in the Basque Country. It was identified how many of them had also depression. The dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 42 publications
(58 reference statements)
4
33
0
Order By: Relevance
“…This is in concordance with data from the general population, as well as from studies conducted in subjects with diabetes from other countries (e.g. 15.1% females vs. 5.2% males in Basque country and 32.3% females vs. 21.8% males in Lithuania, respectively) (9,11,31,32). The gender differences might be explained by hormonal or other biological factors, environmental experiences, including social demands and work burden or to psychological attributes and coping skills related to life events, but this is beyond the scope of the present work (33).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in concordance with data from the general population, as well as from studies conducted in subjects with diabetes from other countries (e.g. 15.1% females vs. 5.2% males in Basque country and 32.3% females vs. 21.8% males in Lithuania, respectively) (9,11,31,32). The gender differences might be explained by hormonal or other biological factors, environmental experiences, including social demands and work burden or to psychological attributes and coping skills related to life events, but this is beyond the scope of the present work (33).…”
Section: Discussionsupporting
confidence: 91%
“…The reported prevalence of depression in subjects with T2D varied largely in similar studies in other geographical areas, from 9.8% in Basque region and 13% in Ethiopia to 40.3% in Malesia and Nepal and 48.27% in Mexico for example, and these differences could potentially be related to methodology, variations in characteristics of the study populations (e.g. duration of diabetes, age) or simply due to genetic/ethnic backgrounds (9,10,(12)(13)(14). In Central and Eastern European countries, the reported rates of depression in patients with diabetes are relatively high: 30.3% in Germany, 29.7% in Poland, 28.4% in Lithuania and 22% in Croatia (11,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In this study, we could see a reduction in the rate of incidence of diabetes-related complications from 2007 to 2011. Adequate control of type 2 diabetes risk factors is high in the Basque population [ 29 ]. In addition, other studies have reported decreasing incidence of several complications such as amputations [ 26 , 30 , 31 ] and preventable hospitalisations [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…10, 11, 12 We therefore aimed to examine the genetic aetiology of the T2DM-depression association in two large population samples of twins using sex-limitation genetic modelling. In this study we combined the data from the Swedish and Danish twin registries, as they have a similar ethnic population structure.…”
Section: Introductionmentioning
confidence: 99%